Proposing new lipoprotein (a) cut off value for Kazakhstan: pilot study - Bekbossynova, Makhabbat; Aripov, Marat; Ivanova-Razumova, Tatyana; Kali, Aknur; Tleubayeva, Dana; Daniyarova, Gulnur; Goncharov, Alexey (Frontiers in Cardiovascular Medicine, 2024)
Introduction There is no consensus on the optimal concentration of lipoprotein(a) (Lp(a)) for the risk of atherosclerotic cardiovascular diseases (ASCVD) and aortic valve stenosis. In various clinical guidelines and agreed documents, the threshold level of Lp (a) is 30 mg/dl or 50 mg/dl. We estimated the cut-off value of Lp (a) associated with the risk of developing various localizations of atherosclerosis for the Central Asia, including Kazakhstani population. Methods This study was conducted at National Research Cardiac Surgery Center, Kazakhstan. 487 patients were included, of which 61.3% were men. The mean age of all participants was 57.3 ± 12.6 years. Bivariate and multivariable logistic regression analysis was used to study the relationship between risk factors and plasma lipoprotein (a) levels. The threshold value of lipoprotein (a) was predicted using the Youden index. Results For Kazakhstani population the lipoprotein (a) cut offs for the risk of developing atherosclerotic CVD and aortic valve calcification was 21.1 mg/dl (p < 0.05). There was no relationship with the level of lipoprotein (a) and low-density lipoprotein cholesterol (LDL-C), which suggests that lipoprotein (a) is an independent risk factor for the development of ASCVD. Discussion This study offers new insights into the threshold value of lipoprotein (a) in Kazakhstan, highlighting its role as a risk factor for atherosclerotic cardiovascular diseases and aortic valve calcification. The findings suggest that the internationally recommended Lp(a) cutoffs may not be suitable for Central Asian populations, as the threshold in our study is significantly lower at 21.2 mg/dL. These results emphasize the need for further research with larger sample sizes to establish more region-specific cutoffs.